Ministry Of Tourism, Arts, Cultures, Youth And Sport Sarawak (Mtacyss)/ Mohd Sukri Comry - Comry, Mohd Sukri (Universiti Teknologi MARA, Sarawak, 2018)
This chapter contains five parts that will be explaining about the organization that I attended to have practical training for eight weeks starting from 24th of July until 15th of September 2017. The first part will explain about background and profile of the organization from its establishment until now. Second part is the functions. This part will elaborate about organizational functions and responsibilities. Third part of this chapter will explains about the organizational strategies, policies, mission and vision. Fourth part will illustrate the organizational structure. It explained the hierarchical order of this organization. Last part will explain the organization core business. It will elaborate on the basic duties and other supplementary duties that the organization do.